2013
DOI: 10.1158/2159-8290.cd-12-0595
|View full text |Cite
|
Sign up to set email alerts
|

PDK1 Signaling Toward PLK1–MYC Activation Confers Oncogenic Transformation, Tumor-Initiating Cell Activation, and Resistance to mTOR-Targeted Therapy

Abstract: Although 3-phosphoinositide-dependent protein kinase-1 (PDK1) has been predominately linked to the phosphoinositide 3-kinase (PI3K)-AKT pathway, it may also evoke additional signaling outputs to promote tumorigenesis. Here, we report that PDK1 directly induces phosphorylation of Polo-like kinase 1 (PLK1), which in turn induces MYC phosphorylation and protein accumulation. We show that PDK1-PLK1-MYC signaling is critical for cancer cell growth and survival, and small-molecule inhibition of PDK1/PLK1 provides an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 122 publications
(130 citation statements)
references
References 41 publications
10
119
1
Order By: Relevance
“…It has previously also been shown that PAX3-FOXO1 has increased posttranslational stability compared with wild-type proteins (21). Our results are furthermore in line with studies demonstrating PLK1 to mediate stabilization of transcription factors such as the oncogene MYC (49). Interestingly, we found the fusion target gene NMYC to be degraded upon PLK1 inhibition, either by a direct or indirect mechanism ( Supplementary Fig.…”
Section: Csupporting
confidence: 91%
“…It has previously also been shown that PAX3-FOXO1 has increased posttranslational stability compared with wild-type proteins (21). Our results are furthermore in line with studies demonstrating PLK1 to mediate stabilization of transcription factors such as the oncogene MYC (49). Interestingly, we found the fusion target gene NMYC to be degraded upon PLK1 inhibition, either by a direct or indirect mechanism ( Supplementary Fig.…”
Section: Csupporting
confidence: 91%
“…Furthermore, our data also revealed that PDPK1 regulates the MYC/IRF4 axis, which is essential for myeloma cell survival (44). Presumably, PDPK1 regulates the expression of c-MYC and IRF4 in myeloma cells, at least in part via PLK1, RSK2, and AKT (25,36,43,44). CCNDs, which are critically important for myelomagenesis, are also regulated by PDPK1, presumably through RSK2-NTKD (1, 2, 25, 33), whereas proapoptotic BIM and BAD, which are essential for apoptosis of hematopoietic cells, are negatively regulated by PDPK1 through the activation of ERK/RSK2 with or without AKT activation.…”
Section: Discussionsupporting
confidence: 54%
“…Our study showed that normal lymphocytes were much less sensitive to BX-912 compared with myeloma cells, and PDPK1 inhibition led to no life-threatening deleterious effect in several clinical trials for human and preclinical studies with animals (40,43,47). For instance, previous study has shown that PDPK1 hypomorphic mice expressing only 10% of the normal level of PDPK1 were viable, fertile, and exhibited no obvious harmful phenotype (48).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…In particular, cell cycle regulators MYCN and PLK1 were detected as EE-EE-EE-Down-EE (Figure 6(a)). This indicates a change of cell-cycle regulation during definitive endoderm cell differentiation (Tan et al, 2013). Additional classification results may be found in Supplementary Note section 3.…”
Section: Spint1 No0mentioning
confidence: 82%